Video and Effectiveness of Leaflets in Breastfeeding Counseling on Breastfeeding Counseling Results in primipara in Yogyakarta in 2010 Mergangsan Health Center - Kusmayra Ambarwati; Nining Wiyati; Sujiyati Sujiyati (Poltekkes Kemenkes Semarang, 2012)
This study is a True experimental designs by using the Post Test With Control Group Design with 51 research subjects primiparous mothers who give birth in health centers Mergangsan with a random sample techniques. This study with primary data using ANOVA. The use of videos and leaflets effective in counseling feeding with p – value (0.00). Effectiveness in the control group and the leaflet is 8.470588, the effectiveness of the leaflets and video group is 10.823529, the effectiveness of the control group and the video is 19.294118. The use of leaflets and video effectively in breastfeeding counseling.